Customer Empowerment and Engagement Behaviours Influencing Value for FinTech Customers: An Empirical Study from India - Nayak Kini, Archana; Basri, Savitha (Organizations and Markets in Emerging Economies, 2023)
The article aims to study the impact of consumer empowerment on customer engagement behaviours (CEBs) and their effect on customer value in the FinTech industry of India. A cross-sectional analytical study was carried out to collect data from 380 Indian FinTech app users using a survey questionnaire. The Partial Least Square Structural Equation Modelling (PLS-SEM) method was applied to test the conceptual model. This is one of the first research studies during the COVID-19 pandemic to show that customer-empowered behaviours predict positive CEBs such as reviews and testimonials, which then contribute to customer value. The indirect effects indicate that CEB mediates the relationship between customer empowerment and value. This study also operationalizes and validates customer engagement behaviour as a formative higher-order construct formed by four dimensions such as customers’ social media influence, form/modality, the scope and channel of engagement. To create customer value, FinTech practitioners and e-marketers should foster online communities and identify and manage customers’ need for control and empowerment for a particular service or product under study thus guiding them in designing customized marketing strategies. The study directs academicians and researchers to build engagement models that can enforce positive CEBs namely e-word of mouth, customer reviews and testimonials.